A new blind genus of Anurophorinae (Collembola: Isotomidae) with seven anal spines from Northwest China - Gao, Yan; Potapov, Mikhail; Bu, Yun (Zootaxa, 2022)
A new genus and species of Anurophorinae, Heptacanthella yinae gen. et sp. nov., is described from Xinjiang Province, Northwest China. The new genus has four spines on Abd. V in p1 and p2 position and three spines on Abd. VI in m0 and m1 position, seven anal spines in all distally on the abdomen. It can be distinguished from other “spined genera” of the subfamily by the position and number of the anal spines. A comparison of spinal armament of last abdominal segments in 13 genera of Anurophorinae is made here. Heptacanthella yinae gen. et sp. nov. is also characterised by the absence of eyes, pigment, furca and retinaculum, presence of reticulated cuticle and an s-formula of 33/22224 (s) and 10/001 (ms). The value of anal spines in taxonomy of Isotomidae is discussed.